2007
DOI: 10.1103/physrevlett.98.236403
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Optical Contrast in Phase-Change Materials

Abstract: Several chalcogenide alloys exhibit a pronounced contrast between the optical absorption in the metastable rocksalt and in the amorphous phase. This phenomenon is the basis for their application in optical data storage. Here we present ab initio calculations of the optical properties of GeTe and Ge1Sb2Te4 in the two phases. The analysis of our computations and experimental data reveal the correlation between local structural changes and optical properties as well as the origin of the optical contrast in these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
128
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 172 publications
(134 citation statements)
references
References 27 publications
(28 reference statements)
4
128
0
2
Order By: Relevance
“…Second, GeTe-rich alloys show larger changes in electronic and optical properties that correlate with the increasing concentration of tetrahedral sp 3 -bonded Ge atoms in these materials. 32 For a-GST-8,2,11, 42% of Ge atoms belong to this category so that 16% of all atoms are not bound octahedrally ͑p 3 ͒. This should increase further for x Ͻ 1 9 .…”
Section: B Electronic Structurementioning
confidence: 99%
“…Second, GeTe-rich alloys show larger changes in electronic and optical properties that correlate with the increasing concentration of tetrahedral sp 3 -bonded Ge atoms in these materials. 32 For a-GST-8,2,11, 42% of Ge atoms belong to this category so that 16% of all atoms are not bound octahedrally ͑p 3 ͒. This should increase further for x Ͻ 1 9 .…”
Section: B Electronic Structurementioning
confidence: 99%
“…When the laser beam is switched off, the melted marks quench into an amorphous state due to the high thermal conductivity of the substrate underneath the phase-change materials. Conversely, the recorded marks are erased when the materials are heated above the glass transition temperature but yet below the melting threshold so that the materials return to the crystalline state [7][8][9][10][11][12][13][14][15][16][17]. For the nonvolatile electrical storage, applying a higher voltage pulse (reset pulse) to the crystalline state with low resistivity leads to the local melting and consequently the formation of an amorphous information bit with high resistivity due to the rapid quenching.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of the phase-change memory, various materials were examined, and the materials of the best performances in terms of speed and stability were found to be GeSbTe (abbreviated as GST) family, such as Ge 2 Sb 2 Te 5 and Ge 1 Sb 4 Te 7 [4,9,16,17,[21][22][23], and AgInSbTe (abbreviated as AIST) family, such as Ag 3.4 [2,3,7,[11][12][13][14][15][24][25][26][27][28]. The thermal properties of GST family were measured and studied in details, and the studies showed that there were common characteristics for different members in the GST family due to the distorted NaCl-type rock structures [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structures in above mentioned are tapered or dome shaped, or even jet shaped, due to volume expansion of the material under laser irradiation. Recently, chalcogenide phase change materials, usually used as optical and electronic data storage media because of the differences in electrical conducting between the crystalline and amorphous states [11], were also found to exhibit similar tapered morphologies upon laser irradiation [12]. Different models have been proposed to explain the formation mechanism of the structures, such as Marangoni convection flow of the melted material [13], material evaporation of the thin film [14], thermoplastic deformation of the film [15], and photomechanical spallation of the upper film [16].…”
Section: Introductionmentioning
confidence: 99%